(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Non-secretory multiple myeloma (NSMM) is an uncommon variation of the classic form of multiple myeloma (MM) that has au analogous clinical and radiologic presentation except for the absence of the M-protein in sernm and/or urine. NSMM may have or not detectable monoclonal free light chain in urine/serum. We describe here a case of a 46-year-old woman who presented with back pain and lower limb weakness. A tumour lesion at DI level and multiple osteolytic bone lesions were found. This woman had no other symptoms and her basic blood biochemistry were nonnal. She had normal serum and urine protein electrophoresis. Biopsy from the D1 vertebra showed plasmocytoma. In the bone marrow, 20% atypical plasma cell fow1d, all were being CD38+ and CD 138+ in flowcytometry, confirming the diagnosis of myeloma presenting as NSMM. A high index of suspicion is needed to diagnose cases like this, as the biology ofNSMM is not completely understood.